Related Strategies to Promote Gastronomy in Geographically Disadvantaged Areas - Maria del Pilar Leal Londoño (Via@)
The present article analyzes State and local level tourism-related strategies to promote traditional cuisine in two geographically disadvantaged areas : two districts in the Catalonian Pyrenees, and two Scottish islands. The article is developed on the basis of a literature review and seven interviews given to a variety of stakeholders involved in the strategies. The results are analyzed following the “four orders” of culinary tourism established by Hjalager (2002). The findings reveal that two, to all appearances, very different territories have some points in common in their strategies to promote their products and, ultimately, attract tourists and visitors through their food resources.